2022
DOI: 10.1007/s11547-022-01520-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of particle radiotherapy on the functioning of cardiac implantable electronic devices: a systematic review of in vitro and in vivo studies according to PICO criteria

Abstract: The number of oncological patients who may benefit from proton beam radiotherapy (PBT) or carbon ion radiotherapy (CIRT), overall referred to as particle radiotherapy (RT), is expected to strongly increase in the next future, as well as the number of cardiological patients requiring cardiac implantable electronic devices (CIEDs). The management of patients with a CIED requiring particle RT deserves peculiar attention compared to those undergoing conventional photon beam RT, mostly due to the potential generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Pacing leads have been regarded as insensitive to radiation by previous reports ( 33 , 44 , 58 ). The pacing leads utilised in ICDs and CRTs are more intricate due to the defibrillation circuits ( 94 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Pacing leads have been regarded as insensitive to radiation by previous reports ( 33 , 44 , 58 ). The pacing leads utilised in ICDs and CRTs are more intricate due to the defibrillation circuits ( 94 ).…”
Section: Discussionmentioning
confidence: 97%
“…To further mitigate CIED malfunctions, manufacturers have been utilising more safety measures in their products; for example, hermetically-sealed metal shielding, signal filtering and nanomagnetic insulation ( 25 , 35 ). Despite these improvements, several studies ( 36 44 ) have indicated that CIED malfunctions can occur via direct or indirect proton beams and their secondary neutron particles manifesting a series of hardware and software malfunctions. Hardware malfunctions represent permanent irreversible damage (including battery issues) to the hardware of the device and require replacement ( 17 , 45 ).…”
Section: Introductionmentioning
confidence: 99%
“… 8 Data from a recent meta-analysis of the in vitro research of particle beam therapy identified 3 key studies as guiding this shift. 15 It is now believed that distance, rather than dose, has a greater impact on CIED function. 7…”
Section: Comparison Between Current Guidelinesmentioning
confidence: 99%
“…Particle therapy, compared with photons, has the potential to further improve the safety profile of STAR by concentrating the therapeutic dose to the target while reducing off-target side effects; with last-generation active scanning particle therapy the potential to interfere with ICDs is very limited. 30 A European consortium named STOPSTORM ( https://stopstorm.eu/ ) has been recently constituted to collect the limited experiences of each centre with the aim to expand the sample size and defined shared operational protocols for patient selection and therapy implementation, which requires a very close collaboration between radiotherapists, radiologists, and electrophysiologists. Currently, STAR should be considered as a bailout therapy for patients with MVT and a dominant clinical morphology either refractory and/or non-candidate to invasive ablation or CSD due to excessive operative risk or other contraindications.…”
Section: Sub-acute/chronic Phasementioning
confidence: 99%